STUDI IMPLEMENTASI PERCEPATAN PEMBANGUNAN KELUARGA SEJAHTERA BERBASIS MASYARAKAT TAHUN 2013 KOTA PEKALONGAN - Hernandika Prayuda; Priyatno Harsasto; Nunik Retno H (Journal of Politic and Government Studies, 2014)
The purpose of this research is to study the implementation of the Accelerating Development of Community-Based Family Welfare Regulation No. 11 of 2008. Seeing the communication, resources, disposition, action. These indicators are then analyzed qualitatively by looking at descriptive understanding was happening. By looking at the various aspects that have analyzed can be concluded that interesting if you look at how the common goals between communities and local governments work together to reach one goal, combating and overcoming poverty in the city of Pekalongan.Keywords: Prevention; poverty; P2KSBM; welfare